2002
DOI: 10.1302/0301-620x.84b6.0840858
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary or intramedullary tibial alignment guides: a randomised, prospective trial of radiological alignment

Abstract: We undertook a prospective, randomised study of 135 total knee arthroplasties to determine the most accurate and reliable technique for alignment of the tibial prosthesis. Tibial resection was guided by either intramedullary or extramedullary alignment jigs. Of the 135 knees, standardised postoperative radiographs suitable for assessment were available in 100. Correct tibial alignment was found in 85% of the intramedullary group compared with 65% of the extramedullary group (p = 0.019). We conclude that intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Reed et al concluded that the use of intramedullary jigs is superior to extramedullary jigs. 11 Dennis et al emphasized that extramedullary guides should be distally positioned over the centre of the talus, 3 mm medial to the midpoint of the ankle rather than right at the midpoint to avoid varus tibial resection. With this technique, 88% of tibial components were aligned within 90 ± 2°.…”
Section: Discussionmentioning
confidence: 99%
“…Reed et al concluded that the use of intramedullary jigs is superior to extramedullary jigs. 11 Dennis et al emphasized that extramedullary guides should be distally positioned over the centre of the talus, 3 mm medial to the midpoint of the ankle rather than right at the midpoint to avoid varus tibial resection. With this technique, 88% of tibial components were aligned within 90 ± 2°.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical advantages and disadvantages of both intramedullary and extramedullary methods are well documented in the literature [5]. The intramedullary method cannot be accurately used in patients who have a history of skeletal trauma and subsequent deformity, neither can the intramedullary method be reliably used in those with retained metal work or used on those with significant natural bowing of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Among surgical techniques, both intra-(IM) and extramedullary (EM) tibial guides have been used to provide the desired lower extremity alignment. However, there are still controversies over the outcome of TKA using either technique to provide a neutral alignment (1,9). Some studies have preferred one for providing a more accurate tibial alignment (9)(10)(11), while the others found no signi cant difference between either technique (1,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%